Một số vấn đề về đẩy mạnh phong trào thể dục thể thao quần chúng hiện nay - Nguyễn, Ngọc Quý (Dạy và học ngày nay, 2023)
This is an activity to thengthen people physical health contribute to enriching spiritual life, and ople to develop comprehted Therefore, the development of physical training and sports in general and mass sporu in frong s policy and social policy of our Party and State. Along with the goal of strengthening and protecting ties and society sport is also one of the solutions to create cohesion and social support towards the